The Chiltern Hills: Baptist Churches and Their Leaders from Early Beginnings to the Hanoverian Regime - Morris, Kate (Baptist quarterly, 2025)
The Chiltern Hills on the borders of Hertfordshire and Buckinghamshire saw a strong Baptist movement from the mid-seventeenth century, perhaps due to their proximity to London but also to the strategic military and trade routes which crossed the territory. The Oxford based Lollards' call for reform in the fifteenth century provided a platform for this and other Dissenting movements in the area. The published Church Books of the Particular Baptists at Kensworth and St Albans and of the General Baptists at Berkhamsted and Chesham together with the still unpublished Church Book of the Particular Baptists at Beechen Grove, Watford provide insights into their communities. These and other sources reveal the origins and development of the Baptist movement across the Northeast Chilterns and towns below. The article reveals new information about Baptist leaders in the region including Thomas Hayward, Edward Harrison and Samuel Ewer.